Longhorned woodboring beetles (Coleoptera, Cerambycidae) from Cusuco National Park, Honduras: new species, new records, and revalidation - Santos-Silva, Antonio; Van Roie, Martijn; Jocqué, Merlijn (European Journal of Taxonomy, 2021)
An ongoing study of the longhorned beetle fauna in the cloud forests of Cusuco National Park revealed multiple additions to the Honduran fauna. Four new species are described: Heterachthes caceresae sp. nov. (Cerambycinae, Neoibidionini), Oreodera kawasae sp. nov. (Lamiinae, Acrocinini), Phrynidius guifarroi sp. nov. (Lamiinae, Apomecynini), and Strangalia lunai sp. nov. (Lepturinae, Lepturini). Additionally, Lagocheirus parvulus Casey, 1913 (Lamiinae, Acanthocinini) is revalidated as Lagocheirus araneiformis parvulus Casey, 1913 (Lagochirus [sic]). We recorded Arixiuna varians (Bates, 1881) (Lamiinae, Hemilophini) for the first time for Honduras. These findings confirm how poorly the invertebrate biodiversity of cloud forests is documented and hints at the large number of species we are losing with the ongoing deforestation.